Evaluation of pharmacology teaching-learning methods in a government medical college - Ghosh, Aritra; Mandal, Krishnendu; Biswas, Suvadip; Dalui, Saikat Kumar; Haldar, Mithilesh; Biswas, Supreeti (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Pharmacology is a major subject in medical science and always changing, so according to it pharmacologists also need to reform their teaching method. Students’ opinion in this evaluation of teaching is a good option. Methods: A questionnaire based study was conducted in Burdwan Medical College on 230 students of two batches. Results: One forty eight students thought that the subject was interesting. Twenty eight percent students opined that Pharmacology class was not interesting. Students found interest mostly in prescription writing, drug interaction and therapeutic problems in practical section. Though 53.4% found pharmacy was less interest. They suggested some reforms in teaching, 61.3% voted for introduction of audio-visual aid and 74.3% response on clinical demonstration in hospital ward. According to 82.6% students, there should be more problem solving exercise during teaching pharmacology; giving hand-out before everyday class, class in clinical setting and more emphasis on clinical pharmacology were also needed. MCQ exam only (31%) and written viva both (51%) were good ways of evaluation according to them. Conclusions: This study helps in knowing students’ opinion and preferences in curriculum to make it more interesting and aids to modify the undergraduate Pharmacology teaching pattern.